Histopathological Spectrum of the Upper Gastrointestinal Tract Endoscopic Biopsies at a Tertiary Hospital: A Descriptive Cross-sectional Study - Shraddha Koirala; Anu Khadka; Suzit Bhusal; Reshika Shrestha; Akanshya Prasai (Journal of Nepal Medical Association, 2024)
Introduction: Upper gastrointestinal tract disorders are prevalent worldwide, encompassing neoplastic and non-neoplastic lesions like infections and inflammation. Endoscopic biopsies play a crucial role in diagnosis, treatment monitoring, and complication detection. Despite their routine use, comprehensive data on their histopathological spectrum is sparse. This study aimed to delineate this spectrum and assess the prevalence of non-neoplastic and neoplastic lesions in upper gastrointestinal tract endoscopic biopsies. Methods: This descriptive cross-sectional study at a tertiary care center analyzed upper gastrointestinal endoscopic biopsies from August 1, 2019, to July 31, 2021. After obtaining ethical clearance (reference number: 039-078/079), we collected all upper gastrointestinal endoscopic biopsies received during the two-year study period, excluding inadequate biopsies, resection specimens, therapeutic cases, and specific lesions.Histopathological examination was conducted using H&E, Giemsa, and Periodic acid-Schiff stains. Diagnoses were categorized into non-neoplastic and neoplastic lesions following WHO guidelines. Data were analyzed using SPSS 16.0 to determine the frequency of neoplastic and non-neoplastic cases. Results: Among 155 upper gastrointestinal biopsies, 124 (80%) were non-neoplastic (95% CI: 73.71-86.29%) and 31 (20%) were neoplastic (95% CI: 13.71-26.29%). Non-neoplastic lesions were predominantly chronic gastritis, with chronic active gastritis being the most frequent 34 (27.41%). Neoplastic lesions were mainly adenocarcinomas in the stomach 20 (64.51%) and squamous cell carcinomas in the esophagus 7 (22.58%). Conclusions: The prevalence of neoplastic lesions were found to lower compared to the published literature and showed predominance of adenocarcinoma in upper gastrointestinal neoplastic lesions.